2012
DOI: 10.1136/bmjqs-2012-001089
|View full text |Cite
|
Sign up to set email alerts
|

Personalised performance feedback reduces narcotic prescription errors in a NICU

Abstract: ObjectiveNeonates are at high risk for significant morbidity and mortality from medication prescribing errors. Despite general awareness of these risks, mistakes continue to happen. Alerts in computerised physician order entry intended to help prescribers avoid errors have not been effective enough. This improvement project delivered feedback of prescribing errors to prescribers in the neonatal intensive care unit (NICU), and measured the impact on medication error frequency.MethodsA front-line multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The reviewers pointed out that, although the median effect of performance feedback might be perceived as small, the 75th percentile effect size was much larger (16 %), suggesting that audit and feedback, when optimally designed and used in the right context, can play an important role in improving professional practice [23]. Sullivan et al [45] reported that a narcotic prescribing error feedback programme in the NICU reduced the errors by 83 % and also increased the time between errors from 3.94 to 22.63 days. They provided group feedback as well as individualised feedback to the clinicians who had prescribed the errors.…”
Section: Discussionmentioning
confidence: 96%
“…The reviewers pointed out that, although the median effect of performance feedback might be perceived as small, the 75th percentile effect size was much larger (16 %), suggesting that audit and feedback, when optimally designed and used in the right context, can play an important role in improving professional practice [23]. Sullivan et al [45] reported that a narcotic prescribing error feedback programme in the NICU reduced the errors by 83 % and also increased the time between errors from 3.94 to 22.63 days. They provided group feedback as well as individualised feedback to the clinicians who had prescribed the errors.…”
Section: Discussionmentioning
confidence: 96%
“…The six intervention types included: technology (n = 38), organizational (n = 16), [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] personnel (n = 13), [72][73][74][75][76][77][78][79][80][81][82][83][84] pharmacy (n = 9), [85][86][87][88][89][90][91][92][93] hazard and risk analysis (n = 8), 10,[93][94][95][96][97][98][99] and multifactorial (i.e. a combination of any of the previous themes; n = 18).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Development of preformatted medication order sheets [56][57][58][59][60][61][62][63][64] Medication distribution and supply (n = 6) Preparation of prediluted medications for administration [65][66][67][68][69][70] Nurse prescribing (n = 1) Transcription of paper-based orders to electronic orders by nursing staff 71 Personnel (n = 13) Staff education (n = 13) Personalized feedback of medication prescribing errors [72][73][74][75][76][77][78][79][80][81][82][83][84] Pharmacy (n = 9) Ward based (n = 6) Interventions identified through introduction of ward-based paediatric/neonatal clinical pharmacy service [85][86][87][88][89][90] Dispensary based (n = 3) Interventions identified through dispensary-based pharmacy service [91][92][93] Hazard and risk analysis (n = 8) Quality improvement tools (n = 4) Use of failure modes, effects, and criticality analyses to redesign care processes 10,[95][96][97] Error detection tools (n = 3) Automated detection of medication errors 93,…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Many studies to reduce PEs and AEs in hospitalized children have investigated the impact of a single intervention such as education or training . The results of those studies showed that none of the interventions were superior in terms of error reduction.…”
Section: What Is Known and Objectivementioning
confidence: 99%